2020
DOI: 10.1186/s12970-020-00345-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural polyphenol-rich pomegranate juice on the acute and delayed response of Homocysteine and steroidal hormones following weightlifting exercises: a double-blind, placebo-controlled trial

Abstract: Background: Maximal strength-speed exercise is a powerful stimulus to acutely increase concentrations of circulating steroid hormones and homocysteine [Hcy]. There is some evidence that antioxidant beverages rich in polyphenols can attenuate [Hcy] levels and modulate endocrine responses in favor of an anabolic environment. Polyphenols-rich pomegranate (POM) have been reported to possess one of the highest antioxidant capacities compared to other purported nutraceuticals and other food stuffs. Studies focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
0
9
0
2
Order By: Relevance
“…The etiology of age-associated cognitive decline is complex and multifactorial with cardiovascular alteration, oxidative stress and neuroinflammation considered major risk factors [10][11][12]. The administration of exogenous antioxidants (e.g., polyphenols) has shown promising findings for reducing the majority of aforementioned risk factors [13][14][15][16][17][18][19]. Additionally, recent reports recognize (poly)phenols as a brain-friendly intervention that may prevent and delay age-associated decline in cognitive function [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of age-associated cognitive decline is complex and multifactorial with cardiovascular alteration, oxidative stress and neuroinflammation considered major risk factors [10][11][12]. The administration of exogenous antioxidants (e.g., polyphenols) has shown promising findings for reducing the majority of aforementioned risk factors [13][14][15][16][17][18][19]. Additionally, recent reports recognize (poly)phenols as a brain-friendly intervention that may prevent and delay age-associated decline in cognitive function [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These (poly)phenol compounds, such as flavonoids, phenolic acids and tannins, are found in varying concentrations in a range of plant-based food sources (e.g., legumes, fruit, vegetables, herbal extracts, spices, coffee, tea and cocoa), and their effects on human health have drawn considerable attention. Specifically, (poly)phenols have been linked to a number of health benefits including modulation of inflammation [14,15], reductions in risk of cardiovascular disease [13,15,18,22], anticancer effects [23] and protection against oxidative stress [16,17]. Concerning the neuroprotective effects, a recent systematic review (SR) and meta-analysis (MA) examining the effects of (poly)phenol-rich supplementation on age-related cognitive decline suggested polyphenol-rich supplementation may improve some cognitive and brain functions in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been reported that pomegranate extract in combination with exercise improves immune function in HFD-fed rats, restoring immunomodulatory factors in serum, inhibiting inflammation and decreasing oxidative stress, compared to the extract or the exercise alone [ 114 ]. Besides, it has been demonstrated that Pomegranate juice slightly reduces muscle damage markers, fatigue, and the recuperation time in elite athletes, which provides additional benefits against skeletal muscle damage and cachexia [ 115 , 116 ].…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…2, (Vol. 16) постоянная усталость, снижение полового влечения, потеря плотности костей, нерегулярные менструации и сухость влагалища. [3] У мужчин пик выработки тестостерона приходится на 18-19 лет, а после 40 лет его синтез снижается на 1-2% в год.…”
Section: низкий уровень тестостерона: симптомы и риски для здоровьяunclassified